The Use of a Novel Quantitative Marker of Echogenicity of Pleural Fluid in Parapneumonic Pleural Effusions - Charalampos Varsamas; Alexandros Kalkanis; Konstantinos I. Gourgoulianis; Foteini Malli (Canadian Respiratory Journal)
Background. Thoracic ultrasound is an essential tool in the daily clinical care of pleural effusions and especially parapneumonic pleural effusions (PPEs), in terms of diagnosis, management, and follow-up. Hypoechogenicity index (HI) is a quantitative marker of pleural fluid echogenicity. We aimed to examine associations of HI with pleural inflammation in patients with PPE. Methods. All patients included underwent a thoracic ultrasound with HI determination at the first day of their admission for a PPE. Thoracentesis was performed in all patients. Demographics, laboratory measurements, and clinical data were collected prospectively and recorded in all subjects. Results. Twenty-four patients with PPE were included in the study. HI was statistically significantly correlated with intensity of inflammation as suggested by pleural fluid LDH (p<0.001, r = −0.831), pleural fluid glucose (p=0.022, r = 0.474), and pleural fluid pH (p<0.001, r = 0.811). HI was correlated with ADA levels (p=0.005, r = −0.552). We observed a statistically significant correlation of HI with pleural fluid total cell number (p<0.001, r = −0.657) and polymorphonuclears percentage (p=0.02, r = −0.590), as well as days to afebrile (p=0.046, r = −0.411), duration of chest tube placement (p<0.001, r = −0.806), and days of hospitalization (p=0.013, r = −0.501). Discussion. HI presents a fast, easily applicable, objective, and quantitative marker of pleural inflammation that reliably reflects the intensity of pleural inflammation and could potentially guide therapeutic management of PPE.